Bishopsquarter church, north door, jamb, arch and hood - O'Donovan, Danielle (My University, 2008)
Door jamb and arch moulding running along chamfer plane, from intrados the elements comprise: quadrant, sunk chamfer, right-angled rebate, sunk chamfer, quadrant. The moulding of the hood also runs along the chamfer plane, comprsing hollow, free-standing fillet, hollow.
Door
Keywords: Architecture, Gothic -- Ireland; Gothic doorways; Late Medieval; moldings, hollow; roll moldings; fillets (moldings); hood moldings